2021
DOI: 10.1186/s40659-021-00363-1
|View full text |Cite
|
Sign up to set email alerts
|

Diosmetin inhibits cell proliferation and promotes apoptosis through STAT3/c-Myc signaling pathway in human osteosarcoma cells

Abstract: Background Diosmetin is a bioflavonoid compound naturally abundant in citrus fruits. It is found to perform a variety of activities, while its antitumor property in osteosarcoma, a malignant tumor with unmet clinical treatment, remained unknown. Methods Colony formation assay, cell cycle analysis and apoptosis analysis were conducted respectively to observe the effect of diosmetin on cell proliferation and apoptosis in human osteosarcoma cells. Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…The results from our study suggested that AEL-sed showed reasonable anticancer effects. Several phytochemicals, such as diosmetin, esculetin, isoacteoside, baicalin, isoamericanol A, luteolin, apigenin, and genkwanin, among several others identified in the extract, have been reported as promising anticancer agents in several in vitro and in vivo studies [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Therefore, A. ebracteatus extract contains several constituents with promising bioactivities that could be beneficial for the treatment of several disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The results from our study suggested that AEL-sed showed reasonable anticancer effects. Several phytochemicals, such as diosmetin, esculetin, isoacteoside, baicalin, isoamericanol A, luteolin, apigenin, and genkwanin, among several others identified in the extract, have been reported as promising anticancer agents in several in vitro and in vivo studies [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Therefore, A. ebracteatus extract contains several constituents with promising bioactivities that could be beneficial for the treatment of several disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the sub G 0 /G 1 phase was previously seen by Salti and collaborators in the HT29 cells with a treatment with GEN 100 µM for 72 h [ 29 ]. In contrast, SW620 cells presented a G 2 /M cell cycle arrest of more than 85% of the cells, which could explain the decrease in cell viability due to the inability of SW620 cells to divide, causing a cytostatic effect of GEN on this cell line [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…c-Myc is a downstream gene regulated by STAT3. The STAT3/c-Myc axis is involved in the oncogenesis, progression, metabolism and therapeutic response of a variety of cancers (34)(35)(36)(37). Haizhi Yu et al found that c-Myc expression levels were increased in patients' T-ALL cells as well as Jurkat and DU528 T-ALL cell lines compared with peripheral blood mononuclear cells (PBMCs) from healthy donors (21).…”
Section: Discussionmentioning
confidence: 99%